Identification of the 5s rDNA locus in Physalis peruviana L. chromosomes, first report (Scientia Agropecuaria, 2021)
Physalis peruviana (Golden berry) a native fruit of Peru, is an important Andean agricultural crop. Although classical cytogenetics research on this berry has been conducted there is no precise evidence based on molecular cytogenetic studies. The Fluorescent In Situ Hybridization (FISH) technique was applied to reveal 5S rDNA sites in chromosomes of San Pablo and Celendín populations, Cajamarca, Perú. This research was identified the 5S rDNA locus in the two populations of Golden berry, reporting six signals in 3 pairs of chromosomes which would indicate that the species is polyploid. Likewise, no differences were found in the number of 5S rDNA loci between both populations, so we could point out that they would not be different ecotypes.
Keywords: Golden Berry; FISH; chromosome; 5S rDNA locus; cytogenetics